Pelatihan Strategi Pembelajaran bagi Guru di SMP 87 Maluku Tengah dalam Upaya Penerapan Pembelajaran yang Inovatif - Lasaiba, Djamila; Ladjamadia, Jawani (Jurnal Pengabdian Arumbai, 2023)
The lack of strategies for teacher learning at SMP 87 Central Maluku is a major challenge. Training is needed to improve pedagogical skills, introduce technology, and overcome time constraints. High school support and student diversity create an ideal environment for the development of innovative learning strategies. The goal is to improve the quality of education by focusing on the unique needs of students in Central Maluku. Community service activities at SMP 87 Central Maluku on July 11, 2023 included a training method with a Forum Group Discussion (FGD) approach. FGD is used for group discussions to develop learning strategies according to student needs. The stages include planning, pre-test, implementation of FGD training, post-test, and evaluation and analysis using paired sample t-tests. The participatory FGD approach is an effective tool to support responsive learning development strategies to student needs. Learning strategy training at SMP 87 Central Maluku has a positive and sustainable impact. Careful planning and active teacher participation reflect a commitment to improving the quality of education. Pre-test and post-test analysis showed significant improvement, supported by high t-test values ​​and low p-values. The implementation of new strategies and teacher-lecturer collaboration created a dynamic learning community for continuous improvement in the school.